In vitro-in vivo availability of metformin hydrochloride-PLGA nanoparticles in diabetic rats in a periodontal disease experimental model - Aline de Sousa Barbosa Freitas Pereira; Maria Laura de Souza Lima; Arnobio Antonio da Silva-Junior; Emanuell dos Santos Silva; Raimundo Fernandes de Araújo Júnior; Agnes Andrade Martins; Jovelina Samara Ferreira Alves; Artur de Santana Oliveira; Leandro De Santis Ferreira; Emily Cintia Tossi de Araújo Costa; Gerlane Coelho Bernardo Guerra; Caroline Addison Carvalho Xavier de Medeiros; et al. (Taylor & Francis Group, 2021)
Context Metformin is an important oral anti-hyperglycemic used in diabetes. Polylactic-co-glycolic acid (PLGA) has been widely used due to its reliability in controlling the release of drugs. Objective This study evaluates the in vitro-in vivo availability of metformin hydrochloride-loaded polylactic-co-glycolic acid. Material and methods In vitro metformin release (Met-free or PLGA + Met-12.5 mg/mL per 360 min) was evaluated using static Franz vertical diffusion cells. The in vivo study was performed with two control groups (validation bioanalytical method) and two experimental groups of diabetic male Wistar rats treated with PLGA + Met 10 mg/kg or Met 100 mg/kg by oral gavage. Diabetes was induced by streptozotocin (40 mg/kg) through the penile vein. Blood samples were collected 0.5, 1, 4, 7, 10, 12, 18, 24, 36, 48 and 72 h and analysed by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Results PLGA + Met 10 mg/kg was released in the in vitro assay suggesting a parabolic diffusion kinetic model (K −0.0619−0.5h) with a 100% release profile in 10 h by controlled diffusion. The in vivo assay showed the apparent volume of distribution Vz/F (PLGA + Met 10 mg/kg, 40971.8 mL/kg vs. Met 100 mg/kg, 2174.58 mL/kg) and mean residence time MRTinf (PLGA + Met 10 mg/kg, 37.66 h vs. Met 100 mg/kg, 3.34 h). Discussion and Conclusions The formulation modifies pharmacokinetics parameters such as apparent distribution volume and mean residence time. The PLGA + Met 10 mg/kg had a slower elimination rate compared to Met 100 mg/kg in diabetic rats in a periodontal disease experimental model.